Fluorescent silica nanoparticles with chemically reactive surface: Controlling spatial distribution in one-step synthesis - Vera, María Laura (2017)
The encapsulation of fluorescent dyes inside silica nanoparticles is advantageous to improve their quality as probes. Inside the particle, the fluorophore is protected from the external conditions and its main emission parameters remains unchanged even in the presence of quenchers. On the other hand, the amine-functionalized nanoparticle surface enables a wide range of applications, as amino groups could be easily linked with different biomolecules for targeting purposes. This kind of nanoparticle is regularly synthesized by methods that employ templates, additional nanoparticle formation or multiple pathway process. However, a one-step synthesis will be an efficient approach in this sort of bifunctional hybrid nanoparticles. A co-condensation sol-gel synthesis of hybrid fluorescent silica nanoparticle where developed. The chemical and morphological characterization of the particles where investigated by DRIFTS, XPS, SEM and SAXS. The nanoparticle fluorescent properties were also assessed by excitation-emission matrices and time resolved experiments. We have developed a one-pot synthesis method that enables the simultaneous incorporation of functionalities, the fluorescent molecule and the amino group, by controlling co-condensation process. An exhaustive characterization allows the definition of the spatial distribution of the fluorescent probe, fluorescein isothiocyanate, inside the particle and reactive amino groups on the surface of the nanoparticle with diameter about 100 nm.